AI-ASSISTED DIGITAL STORYTELLING FOR LEARNING ISLAMIC CIVILIZATION HISTORY; HOW AI-ASSISTED DIGITAL STORYTELLING ENHANCES LEARNING - Maryam Maryam; Arum Puspitasari; Bety Bety; Chairun Niswah; Alimni Alimni (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
Artificial intelligence (AI) opens up new opportunities for learning Islamic history in higher education. However, its use remains largely limited to information retrieval, failing to fully optimize support for students' historical thinking processes. This study aims to analyze the role of AI-assisted digital storytelling in helping students construct historical narratives, verify sources, compare historiographical perspectives, and revise historical interpretations. A qualitative approach with a case study design was employed. Data were collected through interviews, classroom observations, and analyses of students' digital storytelling projects, then analyzed using the Miles and Huberman interactive model. The results indicate that AI-assisted digital storytelling supports learning through four key processes: historical narrative construction, source verification, comparison of historiographical perspectives, and revision of historical interpretations. AI functions not merely as a source of information but also facilitates historical exploration, analysis, evaluation, and reflection. These findings demonstrate that integrating AI into digital storytelling can strengthen students' digital literacy, historical thinking, and interpretation skills within the context of Islamic history education.